Efficiency, fairness and friendliness evaluation of TFRC and ARC rate-based congestion control - L.A. Grieco; S. Mascolo (First International Symposium on Control, Communications and Signal Processing, 2004., 2004)
This paper has focused on two rate-based congestion control algorithms, namely TCP-friendly rate control (TFRC) and the adaptive rate control (ARC), for streaming flows over the Internet. After a brief description of the two algorithms, computer simulations using ns-2 have been reported to investigate intra-protocol fairness, inter-protocol friendliness and efficiency. The main results are given: (1) ARC is friendly towards Reno TCP whereas TFRC is not; (2) ARC increases fairness; (3) ARC remarkably improves the goodput with respect to TFRC and Reno TCP in the presence of wireless lossy links.
Keywords: Programmable control; Adaptive control; Internet; Computer simulation; Proposals; Equations; Throughput; Bandwidth; Phase measurement; Time measurement